Molecular chaperone Hsp90 protects KCBP from degradation by proteasome in Dunaliella salina cells - Shi, Ke; Yang, Liang; Du, Xiuhong; Guo, Dan; Xue, Lexun (Folia microbiologica, 2021)
Kinesin-like calmodulin-binding protein (KCBP) is a unique kinesin with half kinesin and half myosin, with kinesin motor domain at C-terminus and myosin tail homology region 4 (MyTH4) and band 4.1, ezrin, radixin, moesin (FERM) domains at N-terminus. The special structure endows KCBP multi-intracellular functions, including cell division, trichome morphogenesis in plants, and flagellar function in algae. However, little is known about the molecular mechanism underlying these functions. Here, we identified a molecular chaperone Hsp90 as a novel binding partner with KCBP in Dunaliella salina using a yeast two-hybrid screen. Further analysis showed that Hsp90 interacted with both the N-terminal and C-terminal of DsKCBP. Since Hsp90 was involved in the stability and proteolytic turnover of numerous proteins, whether Hsp90 regulated the degradation of DsKCBP was investigated. Our results showed that both Hsp90 and DsKCBP presented in the purified proteasome, and the interaction of DsKCBP-Hsp90 was inhibited upon Hsp90 inhibitor geldanamycin treatment. The level of DsKCBP proteins was diminished remarkably indicating that the disassociation of DsKCBP from Hsp90 accelerated the degradation of the former. Furthermore, immunofluorescence results showed that the localization of DsKCBP at basal body and flagella was disappeared by Hsp90 inhibition. The increased mRNA level of DsKCBP during flagellar assembly was not obvious by geldanamycin treatment. These data provided evidence that Hsp90 protected DsKCBP from degradation by proteasome and was involved in the role of DsKCBP in flagellar assembly.
Keywords: Arabidopsis; molekulární chaperony; Proteasome Endopeptidase Complex; proteiny huseníčku; proteiny vázající kalmodulin; Molecular Chaperones; Calmodulin-Binding Proteins; proteasomový endopeptidasový komplex; Arabidopsis Proteins; kalmodulin; Calmodulin